2013
DOI: 10.4085/1062-6050-48.1.03
|View full text |Cite
|
Sign up to set email alerts
|

Injured Athletes' Rehabilitation Beliefs and Subjective Well-Being: The Contribution of Hope and Social Support

Abstract: Context: Injuries are a significant problem in the world of sports. Hope and social support are very important features in providing psychological help as people face life challenges such as sport injuries.Objective: To examine how hope and social support uniquely and jointly predict postinjury rehabilitation beliefs, rehabilitation behavior, and subjective well-being.Design: Cross-sectional study. Setting: Four sports-injury rehabilitation centers of local universities in Taiwan.Participants: A total of 224 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 29 publications
1
37
0
1
Order By: Relevance
“…Also this investigation is the first to explore the relationships between hope and subjective happiness. Although many studies have suggested that subjective happiness can substantially influence hope (Lu & Hsu, 2013), no research has addressed the factors that might mediate these relationships. In other words, subjective happiness and literature is unclear about how subjective happiness increases hope or vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Also this investigation is the first to explore the relationships between hope and subjective happiness. Although many studies have suggested that subjective happiness can substantially influence hope (Lu & Hsu, 2013), no research has addressed the factors that might mediate these relationships. In other words, subjective happiness and literature is unclear about how subjective happiness increases hope or vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…R = 0.58, p < 0.01. Population: US (students) 53 Lu and Hsu (2013). PANAS positive affect versus ATHS pathways subscale.…”
Section: Appendix: Studies Included In Literature Reviewmentioning
confidence: 99%
“…In recent years, researchers have turned their attention toward understanding positive environments, traits, and subjective experiences in the context of sport injury (e.g., Smith & Sparkes, 2005;Niven, 2007;Tracey, 2011;Lu & Hsu, 2013;Day & Wadey, 2016). This shift in the literature from the dominant focus on the negative consequences of injury has helped provide a greater understanding of athletes' recovery from injury.…”
mentioning
confidence: 99%